2007
DOI: 10.1016/j.ejcts.2007.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of right-sided active infective endocarditis with or without involvement of the left heart: 20-year single center experience☆

Abstract: Our surgical strategy for right-sided infective endocarditis is based on three principles: (1) debridement of the infected area or vegetectomy; (2) valve repair whenever possible, avoiding artificial material; (3) if valve replacement is unavoidable, use of a biological substitute without any artificial material that might become infected. Following these strategies surgery of right-sided infective endocarditis with or without left-side involvement can be performed with good early, mid-term and long-term resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 23 publications
6
94
1
1
Order By: Relevance
“…It is assumed that there is a dynamic combination of host, environmental, immunological and microbial factors acting in concert to cause predominantly RSIE in this population, with specific factors contributing relatively more or less in any individual patient (10). Once the valve has been infected and damaged or replaced, repeated episodes of IE occur ever more frequently in IVDUs, with reinfection of up to 28% (5). One study reported a long-term cumulative incidence of reoperation of 20% in IVDU, as opposed to less than 5% in non-users (9).…”
Section: Intravenous Drug Usersmentioning
confidence: 99%
See 4 more Smart Citations
“…It is assumed that there is a dynamic combination of host, environmental, immunological and microbial factors acting in concert to cause predominantly RSIE in this population, with specific factors contributing relatively more or less in any individual patient (10). Once the valve has been infected and damaged or replaced, repeated episodes of IE occur ever more frequently in IVDUs, with reinfection of up to 28% (5). One study reported a long-term cumulative incidence of reoperation of 20% in IVDU, as opposed to less than 5% in non-users (9).…”
Section: Intravenous Drug Usersmentioning
confidence: 99%
“…Higher priority of surgery (emergency vs. urgent vs. elective) could be pointed to as an independent risk factor for early mortality as well (5).…”
Section: Post-operative Outcomesmentioning
confidence: 99%
See 3 more Smart Citations